2021
DOI: 10.15316/sjafs.2021.250
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Income of Farmers Participating In Traditional and Modern Livestock Markets: Case Study from Benin Republic

Abstract: The development of many African countries' economy and life of the rural population in the south of the Sahara depends on the agricultural sector. Seventy to 80% of the active population was employed in the agricultural sector. The contribution of the agricultural sector to the Gross Domestic Product (GDP) of these countries ranged from 30% to 50%. The rural population in these countries has lived under low life standards and in economically unfavourable conditions (Diallo, 2004). In Benin Republic, economic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Ninh (2020) and Roches et al (2016) revealed that education influences farmers' ability to use new technologies, facilitate access to market information, and improve livestock management. The main income for farmers is the sales of their animal livestock; thus they develop rearing plans to maximize earnings (Akouegnonhou and Demirbas 2021). Swine farming is economically profitable if the production costs can be minimized (Bjornlunc et al 2019); therefore, farmers can use household organic waste for feed to feed efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Ninh (2020) and Roches et al (2016) revealed that education influences farmers' ability to use new technologies, facilitate access to market information, and improve livestock management. The main income for farmers is the sales of their animal livestock; thus they develop rearing plans to maximize earnings (Akouegnonhou and Demirbas 2021). Swine farming is economically profitable if the production costs can be minimized (Bjornlunc et al 2019); therefore, farmers can use household organic waste for feed to feed efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…As for rural electrification, access to biogas in rural areas of Sub-Saharan Africa is achieved in the form of PPP, where households order their digester directly from private entrepreneurs. There have been different attempts to expand the development of biogas in rural areas without much success [34], despite its good potential. For example, for a family of 10, the technical potential corresponds to the possibility for households to collect 30 kg of cow dung daily and enough water.…”
Section: Access To Biogas and Ppp In Rural Areasmentioning
confidence: 99%
“…Due to the limited number of cattle on their farms, cattle farmers did not earn a substantial income from farming. Akouegnonhou and Demirbaş (2021) stated that livestock farmers make most of their money from selling animals, which usually happens at livestock markets. The amount of money their family earns relies on the number of cattle they own.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Farmers in rural areas who have extensive experience producing animals can earn significantly more in revenue. It means that a lot of experience with cattle farming could lead to considerable household income (Akouegnonhou and Demirbaş, 2021). The difference seen could be because the settings are in different socioeconomic situations (Seid et al, 2020).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%